Factors Influencing Customer Saving Behavior at PD. BPR Rokan Hilir, Kubu Branch, Rokan Hilir Regency - Rokiyah, Rokiyah (International Journal of Environmental, Sustainability, and Social Science, 2026)
This study examines the Factors Influencing Customer Saving Behavior at Pd. BPR Rokan Hilir, Kubu Branch, Rokan Hilir Regency. This research is a quantitative study where the independent variables used are personal factors, social factors, psychological factors, cultural factors, and customer behavior. Furthermore, its validity is developed or proven empirically based on data collection from the field. Based on the analysis above, it can be seen that the influence of personal factors on the customer behavior, It indicates that personal factors significantly influence customer behavior. The influence of the independent variable, social factors, on the dependent variable, behavior. It indicates that social factors significantly influence customer behavior at PD. BPR Rokan Hilir, Kubu Branch. The influence of psychological factors, customer behavior. It indicates that psychological factors significantly influence customer behavior. The influence of cultural factors variable, customer behavior. It indicates that cultural factors significantly influence customer behavior. The simultaneous influence of Personal Factors, Social Factors, Psychological Factors, and Cultural Factors, on customer behavior significantly influences customer savings behavior at PD. BPR Rokan Hilir, Kubu Branch. The simultaneous influence of Personal Factors, Social Factors, Psychological Factors, and Cultural Factors, on customer savings behavior at PD. BPR Rokan Hilir, Kubu Branch.